2018
DOI: 10.18295/squmj.2018.18.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic Granuloma in an Atypical Location Following Isotretinoin Treatment

Abstract: Interesting Medical Image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…[5][6][7] Barrales et al reported a case of an 18-years-old female taking 30 mg/day of oral isotretinoin for severe acne had multiple ulcerated exophytic dome shaped lesions prone to haemorrhage in the intergluteal fold and pubic region. 8 Diagnosis of pyogenic granuloma was supported by histopathology findings. This was observed again in a trial of 16 total patients of which three patients were reported to have developed proliferative granulation tissue at the sites of previous acne lesions.…”
Section: Discussionmentioning
confidence: 93%
“…[5][6][7] Barrales et al reported a case of an 18-years-old female taking 30 mg/day of oral isotretinoin for severe acne had multiple ulcerated exophytic dome shaped lesions prone to haemorrhage in the intergluteal fold and pubic region. 8 Diagnosis of pyogenic granuloma was supported by histopathology findings. This was observed again in a trial of 16 total patients of which three patients were reported to have developed proliferative granulation tissue at the sites of previous acne lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Most of them were periungual (lateral and distal nail folds), but there were also cases arising on the head, trunk, or upon prior acneic lesions [ 2 , 3 ]. There is only one report of multiple anogenital PGs in a young female that appeared during isotretinoin treatment, requiring dose modification [ 5 ]. However, in our case, the development of PGs occurred three months after the completion of isotretinoin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PGs may be seen at different areas including the head, neck, and extremities or in the oral mucosa cavity during pregnancy [3][4][5][6]. Vulvar PG is a rare finding, and to our best knowledge, only twelve cases in adult female population have been described in the literature [3,4,[6][7][8][9][10][11][12]. Herein, we introduce the first vulvar PG in an Iranian female patient and a brief review of the literature in this regard.…”
Section: Introductionmentioning
confidence: 99%